Oficinas Itinerantes: uma ideia, um obstáculo, um movimento constituinte de subjetividades - Araújo, Aline Miranda Schwartz de (2011)
The Concept of Workshop on health and education has been gradually developed and the action that unfolds it has been widely used in health centers CAPS schools and other devices that are in place. In this paper, we added an adjective to 'Workshop as TRAVELING. This is a reflection made from some questions that arose when we were ministering therapeutic workshops in an old house in a neighborhood of the city of Uberlandia/Minas Gerais (Brazil), in its huge backyard. This was a safe place saved from foreign or surprised outsiders-looks. Perhaps, it s still hidden, but occupying an intermediate place between the inside and outside. However, ‗there was a stone in the middle of the path , the clinic has gone through a crisis and decided to close the doors. We decided to develop the workshops in various parts of the town. Our experience has its anchorage in Fabio Herrmann s studies, which introduces us to Extensive Clinic, which is the extension of the psychoanalytic method to the world, i.e., for the production of human senses. And the geography of Milton Santos said, ‗everything is subject to the law of motion and renovation, including the sciences. The new is not invented, it is discovered . Our question is: after the limited space of the ‗craziness brought in the scientific, social and cultural concepts, how its private space and subjective elements can be re-built in a contemporary society? Entering the field of dialogue between two sciences, two Brazilian contemporary authors, engaged with both reflections, we aim to access and build knowledge from the relationships that arise from streets of a city that needs to be reinvented for daring to reclaim their humanity.